Knock-in Kcnh2 rabbit model of long QT syndrome type-2, epilepsy, and sudden death - Veronica Singh; Kyle T. Wagner; Laura G. Williams; Justin M. Ryan; Katherine R. Keller; Jonathan D. Mohnkern; Robert S. Gardner; Louis T. Dang; Julie M. Ziobro; Richard J. H. Wojcikiewicz; Nathan R. Tucker; David S. Auerbach (Journal of Translational Medicine)
Abstract Background Long QT Syndrome Type-2 (LQT2) is due to loss-of-function KCNH2 variants. KCNH2 encodes Kv11.1 that forms a delayed-rectifier potassium channel in the brain and heart. LQT2 is associated with arrhythmias, seizures, sudden cardiac death, and sudden unexpected death in epilepsy (SUDEP). The goal of the study is to develop a translational model that reproduces the neuro-cardiac electrical abnormalities and sudden death seen in people with LQT2. Methods We generated the first knock-in rabbit model of LQT2 (Kcnh2 (+/7bp−del)), due to a 7 base-pair (7bp) deletion in the pore domain of the endogenous rabbit Kcnh2 gene. Results Mutant Kcnh2 is expressed in the heart and brain and constitutes 11% of total Kcnh2 in Kcnh2 (+/7bp−del) rabbits. Total Kcnh2, WT Kcnh2, and WT Kv11.1 expression is lower in Kcnh2 (+/7bp−del) vs. WT rabbits. Kcnh2 (+/7bp−del) rabbits exhibit prolonged cardiac ventricular repolarization (QTc, JTec, JTpc). There is an increased prevalence of spontaneous epileptiform activity and clinical seizures in Kcnh2 (+/7bp−del) (7 of 37 rabbits) vs. WT rabbits (1:68 rabbits, p < 0.003). 18.9% of Kcnh2 (+/7bp−del) vs. 1.5% of WT rabbits died suddenly and spontaneously (p < 0.003). We recorded 2 spontaneous lethal events in Kcnh2 (+/7bp−del) rabbits: (1) sudden cardiac death and (2) seizure-mediated sudden death due to generalized tonic-clonic seizures, post-ictal generalized EEG suppression, bradycardia, ECG-T-wave inversion, focal cardiac activity, and asystole/death. Conclusions We developed the first genetic rabbit model of LQT2 that reproduces the cardiac and epileptic phenotypes seen in people with LQT2. Kcnh2 (+/7bp−del) rabbits provide a valuable tool for future mechanistic studies, development of neurotherapeutics, and cardiac-safety testing.